Is an Auditor's Propensity to Issue Going Concern Opinions a Valid Measure of Audit Quality?. Issue 2 (18th March 2020) - Guo, Yihan; Delaney, Deborah; Ahmed, Ammad
Abstract: A number of previous studies use auditor propensity to issue a going concern opinion (GCO) as a proxy of audit quality when examining a sample of financially distressed firms. This study examines whether audit quality (measured by discretionary accruals) influences the probability of financially distressed firms receiving GCOs using a non‐specific sample of 2937 firm‐year observations from Australia over the period 2011–2015. The study first investigates the association between financially distressed firms and the issuance of GCOs. This association is then re‐tested after separating the total sample into low and high audit quality subsamples. The results indicate that financially distressed firms are more likely to receive GCOs, confirming the application of ASA 570 Going Concern . However, financially distressed firms that receive GCOs from their auditors are limited to firms that have higher‐quality audits. Abstract : This study investigates the validity of the auditor's propensity to issue a Going Concern Opinion (GCO) as a proxy for audit quality by empirically examining the relationship between audit quality and the probability of a financially distressed firm receiving a GCO. The results of this study indicate that GCO is not a valid proxy of audit quality.